Respuesta :
Answer:
Step-by-step explanation:
3-(2x-5)=-4(x+2)
We simplify the equation to the form, which is simple to understand
3-(2x-5)=-4(x+2)
Remove unnecessary parentheses
3-2x+5=-4*(x+2)
Reorder the terms in parentheses
3-2x+5=+(-4x-8)
Remove unnecessary parentheses
+3-2x+5=-4x-8
We move all terms containing x to the left and all other terms to the right.
-2x+4x=-8-3-5
We simplify left and right side of the equation.
+2x=-16
We divide both sides of the equation by 2 to get x.
x=-8
Answer:
x < - 8
Step-by-step explanation:
Given
3 - (2x - 5) < - 4(x + 2) ← distribute parenthesis on both sides
3 - 2x + 5 < - 4x - 8
- 2x + 8 < - 4x - 8 ( add 4x to both sides )
2x + 8 < - 8 ( subtract 8 from both sides )
2x < - 16 ( divide both sides by 2 )
x < - 8